2016
DOI: 10.1155/2016/6768274
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of Autologous Bone Marrow Stem Cell Transplantation in Patients with Spinal Cord Injury

Abstract: Introduction. A total of 18 patients, with complete motor deficits and paraplegia caused by thoracic and lumbar spine trauma without muscle atrophy or psychiatric problems, were included into this study. Materials and Methods. The bone marrow was aspirated from the anterior iliac crest under local anesthesia and the mononuclear fraction was isolated by density gradient method. At least 750 million mononuclear-enriched cells, suspended in 2 mL of saline, were infused intrathecally. Results and Discussion. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 36 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…A number of clinical studies concerning cell therapies with a positive outcome have led to the suggestion that combination cell therapies and/or certain transplantation approaches with rehabilitation can be more effective 107 , 123 , 128 130 , 136 , 138 …”
Section: Provisionsmentioning
confidence: 99%
“…A number of clinical studies concerning cell therapies with a positive outcome have led to the suggestion that combination cell therapies and/or certain transplantation approaches with rehabilitation can be more effective 107 , 123 , 128 130 , 136 , 138 …”
Section: Provisionsmentioning
confidence: 99%
“…When used as grafts, these cells have the potential for clinical autologous transplantation, without the risk of severe immune rejection. Clinical investigations have indicated that the transplantation of autologous MSCs is feasible and safe [47][48][49][50] . PLGA has been widely used as an artificial catheter, drug controlled-release carrier, and tissue engineering scaffold material for its mechanical properties and biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…More evidence of improving function for patients with complete chronic SCI has been reported using a variety of different cell-based therapies, including umbilical cord blood-derived mononuclear cell transplants for spinal cord and locomotor training, 30 the mononuclear-enriched bone marrow cell transplantation through intrathecal infusion, 31 bone marrow MSC transplantation through lumbar puncture into subarachnoid space, 32 a combination of neuronal cells differentiated from autologous adipose tissue-derived mesenchymal stem cells, and hematopoietic stem cells through intrathecal infusion, 33 and olfactory mucosa lamina propria transplants into the spinal cord. 34 Promising results for patients with ALS have been reported by intraspinal injection of bone marrow-derived neural stem cells, in which patients experienced a temporary stabilization for the first few months postinjection and then gradually deteriorated.…”
Section: New Clinical Evidence For Neurorestorative Strategies Cell Tmentioning
confidence: 99%